Medieval India : the study of civilization - Habib, Irfan, 1931- (New Delhi : National Book Trust, 2007)
Covers the period, 600 A.D. to 1750 A.D.
Includes bibliographical references (p. [261]-273) and index.
Keywords: India -- Civilization